A preparation process of polypropylene composite material
By adding cyclodextrin flame retardant and modified inorganic filler to the polypropylene material, the problems of poor flame retardancy, wear resistance and antibacterial properties of polypropylene materials are solved, and the excellent performance of polypropylene composite materials is achieved, which broadens its application fields.
Patent Information
- Application Number
- CN202410662284.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-05-27
AI Technical Summary
Polypropylene materials have poor flame retardancy, wear resistance and antibacterial properties, which limit their use in certain application areas.
During the preparation of polypropylene material, cyclodextrin flame retardant and modified inorganic filler are added, and polypropylene composite materials with excellent flame retardancy, wear resistance and antibacterial properties are prepared through high-speed stirring and process processing of twin screw extruder.
It effectively improves the flame retardant properties, wear resistance and antibacterial properties of polypropylene materials, and broadens its application areas, especially in the fields of rail transit equipment and rail engineering construction.
Smart Images

Figure CN118388881B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a preparation process of a polypropylene composite material. Background Art
[0002] Polypropylene is a polymer compound formed by the polymerization of propylene through addition polymerization. It has the characteristics of low density, low cost, odorless, non-toxic, corrosion-resistant, good electrical insulation, and excellent mechanical properties. Of course, polypropylene also has some disadvantages, such as poor cold resistance, low low-temperature impact strength, and easy aging due to the effects of light, heat and oxygen, which limits its application range. In order to improve the performance of polypropylene, researchers have improved its performance by adding some functional additives during the preparation process of polypropylene, which has greatly broadened the application field of polypropylene materials and made it widely used in daily household furniture, small appliances, electrical appliances, packaging materials, auto parts, pipes and other fields.
[0003] The invention patent with application number 202010849961.5 discloses an impact-resistant and aging-resistant glass fiber reinforced polypropylene composite material and its preparation method. The patent loads metal oxides onto molecular sieves, and then modifies them with a silane coupling agent. The prepared modified loaded molecular sieves are added to glass fiber reinforced polypropylene composite materials to improve the impact resistance and aging resistance of the composite materials. This preparation method is simple, easy, low-cost, suitable for industrial production, and is widely used in rail transit equipment and rail engineering construction.
[0004] In addition, polypropylene itself is easy to burn, and there will be melt dripping when burning, and a large amount of toxic gas will be released, threatening people's life and property safety. When polypropylene is used in auto parts, small household appliances, electrical appliances, pipes, etc., it is easy to wear due to its low surface hardness. Therefore, it needs to be modified to improve its flame retardancy and wear resistance. When polypropylene is used in the fields of daily household furniture, pipes, packaging materials, etc., it is also necessary to have antibacterial properties to prevent microbial contamination and avoid health hazards to consumers. Based on this, the present invention provides a preparation process of a polypropylene composite material. By adding a cyclodextrin flame retardant and a modified inorganic filler in the preparation process of the polypropylene material, the polypropylene material has excellent flame retardancy, wear resistance and antibacterial properties. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation process of a polypropylene composite material, which solves the problem that the polypropylene material has poor flame retardancy, wear resistance and antibacterial properties.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A preparation process of a polypropylene composite material comprises the following steps:
[0008] The first step is to put 50-80 parts by weight of polypropylene, 10-15 parts of cyclodextrin flame retardant, 0.5-1 parts of lubricant, 1-2 parts of antioxidant and 20-30 parts of modified inorganic filler into a high-speed mixer for mixing, and stir at a speed of 1000-1200 r / min for 0.5-1h. After the stirring is completed, a mixture is obtained;
[0009] The second step is to place the mixture in a twin-screw extruder for melt extrusion, control the temperature of the twin-screw extruder to be 160-200°C, and the speed of the screw to be 150-300r / min. After melt extrusion, the mixture is cut, granulated, and dried to obtain a polypropylene composite material.
[0010] Further preferably, in the first step, the lubricant is any one of magnesium stearate, zinc stearate or sodium stearate; and the antioxidant is any one of antioxidant 1010 or antioxidant 168.
[0011] Further preferably, in the first step, the method for preparing the cyclodextrin flame retardant comprises the following steps:
[0012] S1: Add β-cyclodextrin and N,N-dimethylformamide to a reaction bottle equipped with a thermometer and nitrogen, mix well, then add 1,3,5-triglycidyl-S-triazinetrione and a catalyst, raise the system temperature to 70-80°C, keep the temperature for 10-14h, and after the reaction is completed, remove the solvent by vacuum distillation to obtain modified cyclodextrin;
[0013] S2: Add modified cyclodextrin and tetrahydrofuran to a reaction bottle equipped with a thermometer, mix well, then add dimethyl chlorophosphate and an acid binding agent, raise the system temperature to 55-60°C, keep the temperature for 2-4 hours, and after the reaction is completed, remove the solvent by vacuum distillation to obtain a cyclodextrin flame retardant.
[0014] Further preferably, in step S1, the catalyst is any one of boron trifluoride etherate or tetrabutylammonium bromide.
[0015] More preferably, in step S2, the acid binding agent is any one of triethylamine or pyridine.
[0016] In the above technical scheme, due to the catalytic effect of the catalyst, the hydroxyl groups in the β-cyclodextrin structure can undergo a ring-opening reaction with the epoxy groups in the 1,3,5-triglycidyl-S-triazinetrione structure, and active hydroxyl groups are also generated while introducing the nitrogen element, thereby obtaining a modified cyclodextrin. The active hydroxyl groups in the structure can react with the phosphorus oxychloride in the dimethyl chlorophosphate structure, thereby introducing the flame retardant element phosphorus into the structure of β-cyclodextrin, and utilizing an acid binding agent to absorb HCl generated during the reaction, thereby obtaining a cyclodextrin flame retardant.
[0017] Further preferably, in the first step, the method for preparing the modified inorganic filler comprises the following steps:
[0018] A: Add talcum powder and water to a reaction bottle equipped with a thermometer, perform ultrasonic dispersion, then add 2,3-epoxypropyltrimethylammonium chloride, raise the system temperature to 60-70°C, and keep the reaction for 3-4 hours. After the reaction is completed, filter and separate the solid product, wash, and vacuum dry to obtain modified talcum powder;
[0019] B: Add modified talcum powder and ethanol to a reaction bottle equipped with a thermometer, stir evenly, then add guanidine hydrochloride, raise the system temperature to 55-65°C, and keep the reaction warm for 4-6 hours. After the reaction is completed, filter, wash, vacuum dry, grind and sieve to obtain a modified inorganic filler.
[0020] Further preferably, in step A, the power of the ultrasound is 200-300 W, and the time is 15-20 min.
[0021] Further preferably, in step B, the mesh size of the sieving is 2000-3000 mesh.
[0022] In the above technical scheme, talc is modified by using 2,3-epoxypropyltrimethylammonium chloride, and epoxy groups are introduced into the structure of talc to obtain modified talc. Then, through the ring-opening addition reaction between epoxy groups and amino groups in the guanidine hydrochloride structure, guanidine groups are grafted into talc to obtain modified inorganic fillers.
[0023] Beneficial effects of the present invention:
[0024] (1) The present invention prepares a cyclodextrin flame retardant and adds it to the preparation process of the polypropylene material, thereby effectively improving the flame retardant properties of the polypropylene material. β-cyclodextrin, as a carbon source in the flame retardant, is hydrophilic and has poor compatibility with the polypropylene matrix. By modifying the β-cyclodextrin, the number of hydroxyl groups in its structure is reduced, and the surface property is changed from hydrophilic to lipophilic, thereby improving the dispersibility of β-cyclodextrin in the polypropylene matrix. When the polypropylene composite material burns, the cyclodextrin flame retardant releases non-combustible gas, which can dilute the oxygen concentration around the combustion zone and promote the formation of a dense carbon layer on the surface of the composite material. The strong barrier effect of the carbon layer can effectively inhibit the combustion, thereby achieving the flame retardant properties of the polypropylene composite material.
[0025] (2) The present invention modifies talcum powder and then grafts guanidine hydrochloride to obtain a modified inorganic filler, and the modified inorganic filler is used as a functional auxiliary agent in the preparation of polypropylene materials. On the one hand, talcum powder can reduce the friction coefficient and improve the wear resistance of polypropylene materials. On the other hand, talcum powder has a unique layered structure and can form a heat insulation layer when the polypropylene composite material burns, which can enhance the flame retardant properties of the polypropylene material to a certain extent. After the talcum powder is modified to have antibacterial properties, the guanidine group introduced into its structure has high activity and can effectively inhibit the division and proliferation of bacteria, thereby improving the antibacterial properties of the polypropylene material and greatly broadening the application field of the polypropylene material.
[0026] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0028] Figure 1 The infrared spectra of β-cyclodextrin, modified cyclodextrin and cyclodextrin flame retardant in Example 1 of the present invention are shown.
[0029] Figure 2 This is a thermal gravimetric curve of talc powder, modified talc powder and modified inorganic filler in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] 1. Preparation of cyclodextrin flame retardant
[0033] S1: In a reaction bottle equipped with a thermometer and nitrogen, add 5g of β-cyclodextrin and 100mL of N,N-dimethylformamide, mix well, then add 6.5g of 1,3,5-triglycidyl-S-triazinetrione and 0.4g of boron trifluoride ether, raise the system temperature to 80°C, keep the reaction for 12h, and after the reaction is completed, remove the solvent by reduced pressure distillation to obtain modified cyclodextrin;
[0034] S2: In a reaction bottle equipped with a thermometer, add 3.2g of modified cyclodextrin and 50mL of tetrahydrofuran, mix well, then add 1.4g of dimethyl chlorophosphate and 0.8g of triethylamine, raise the system temperature to 60°C, keep the reaction for 3h, and after the reaction is completed, remove the solvent by vacuum distillation to obtain a cyclodextrin flame retardant.
[0035] The chemical structures of β-cyclodextrin, modified cyclodextrin and cyclodextrin flame retardant were analyzed by Nicolet 5700 Fourier transform infrared spectrometer. Figure 1 As shown, compared with β-cyclodextrin, the modified cyclodextrin has a -1 The stretching vibration absorption peak of C=O appears at 1332cm -1 The stretching vibration absorption peak of CN appears at 1136cm -1 The absorption peak area of COC at 3381 cm-1 is larger than that of modified cyclodextrin. -1 The absorption peak area of hydroxyl group becomes smaller, at 1185cm -1 The stretching vibration absorption peak of P=O appears at 1078cm -1 The stretching vibration absorption peak of COP appears at
[0036] 2. Preparation of modified inorganic fillers
[0037] A: In a reaction bottle equipped with a thermometer, add 6g of talc and 120mL of water, and ultrasonically disperse for 20min at a power of 300W, then add 3.8g of 2,3-epoxypropyltrimethylammonium chloride, raise the system temperature to 60°C, and keep the reaction for 4h. After the reaction is completed, filter and separate the solid product, wash, and vacuum dry to obtain modified talc;
[0038] B: In a reaction bottle equipped with a thermometer, add 4.6g of modified talc and 80mL of ethanol, stir evenly, then add 1.3g of guanidine hydrochloride, raise the system temperature to 55°C, and keep the reaction for 6h. After the reaction is completed, filter, wash, vacuum dry, grind, and pass through a 3000 mesh sieve to obtain a modified inorganic filler.
[0039] Thermogravimetric analysis of talc, modified talc and modified inorganic filler was performed using a TG209F3 thermogravimetric analyzer. Figure 2 As shown, the final residual weight of talc is 96.3%, which is mainly due to the reduction of moisture on the surface of talc. The final residual weight of modified talc is 84.7%, which is mainly due to the thermal decomposition of the epoxy groups modified on the modified talc. The final residual weight of the modified inorganic filler is 71.5%, indicating that talc has successfully achieved antibacterial modification.
[0040] 3. Preparation of polypropylene composite materials
[0041] The first step is to put 50 parts by weight of polypropylene, 10 parts of cyclodextrin flame retardant, 0.5 parts of zinc stearate, 1 part of antioxidant 168 and 20 parts of modified inorganic filler into a high-speed mixer for mixing, and stir at a speed of 1000 r / min for 0.5 h. After the stirring is completed, a mixture is obtained;
[0042] The second step is to place the mixture in a twin-screw extruder for melt extrusion, control the temperature of the twin-screw extruder to 160°C, and the speed of the screw to 150r / min. After melt extrusion, the mixture is cut, granulated, and dried to obtain a polypropylene composite material.
[0043] Example 2
[0044] Preparation of polypropylene composite materials
[0045] The first step is to put 65 parts by weight of polypropylene, 12 parts of cyclodextrin flame retardant, 0.8 parts of zinc stearate, 1.5 parts of antioxidant 168 and 25 parts of modified inorganic filler into a high-speed mixer for mixing, and stir at a speed of 1100 r / min for 1 hour. After the stirring is completed, a mixture is obtained;
[0046] The second step is to place the mixture in a twin-screw extruder for melt extrusion, control the temperature of the twin-screw extruder to 180°C, and the speed of the screw to 200r / min. After melt extrusion, the mixture is cut, granulated, and dried to obtain a polypropylene composite material.
[0047] The preparation methods of the cyclodextrin flame retardant and the modified inorganic filler are the same as those in Example 1.
[0048] Example 3
[0049] Preparation of polypropylene composite materials
[0050] The first step is to put 80 parts by weight of polypropylene, 15 parts of cyclodextrin flame retardant, 1 part of zinc stearate, 2 parts of antioxidant 168 and 30 parts of modified inorganic filler into a high-speed mixer for mixing, and stir at a speed of 1200 r / min for 1 hour. After the stirring is completed, a mixture is obtained;
[0051] The second step is to place the mixture in a twin-screw extruder for melt extrusion, control the temperature of the twin-screw extruder to 200°C, and the speed of the screw to 300r / min. After melt extrusion, the mixture is cut, granulated, and dried to obtain a polypropylene composite material.
[0052] The preparation methods of the cyclodextrin flame retardant and the modified inorganic filler are the same as those in Example 1.
[0053] Comparative Example 1
[0054] Preparation of polypropylene composite materials
[0055] The first step is to put 80 parts by weight of polypropylene, 1 part of zinc stearate, 2 parts of antioxidant 168 and 30 parts of modified inorganic filler into a high-speed mixer for mixing, and stir at a speed of 1200 r / min for 1 hour. After the stirring is completed, a mixture is obtained;
[0056] The second step is to place the mixture in a twin-screw extruder for melt extrusion, control the temperature of the twin-screw extruder to 200°C, and the speed of the screw to 300r / min. After melt extrusion, the mixture is cut, granulated, and dried to obtain a polypropylene composite material.
[0057] The preparation method of the modified inorganic filler is the same as that of Example 1.
[0058] Comparative Example 2
[0059] Preparation of polypropylene composite materials
[0060] The first step is to put 80 parts by weight of polypropylene, 15 parts of cyclodextrin flame retardant, 1 part of zinc stearate and 2 parts of antioxidant 168 into a high-speed mixer for mixing, and stir at a speed of 1200 r / min for 1 hour. After the stirring is completed, a mixture is obtained;
[0061] The second step is to place the mixture in a twin-screw extruder for melt extrusion, control the temperature of the twin-screw extruder to 200°C, and the speed of the screw to 300r / min. After melt extrusion, the mixture is cut, granulated, and dried to obtain a polypropylene composite material.
[0062] The preparation method of the cyclodextrin flame retardant is the same as that in Example 1.
[0063] Comparative Example 3
[0064] Preparation of polypropylene composite materials
[0065] The first step is to put 80 parts by weight of polypropylene, 15 parts of cyclodextrin flame retardant, 1 part of zinc stearate, 2 parts of antioxidant 168 and 30 parts of talc into a high-speed mixer for mixing, and stir at a speed of 1200 r / min for 1 hour to obtain a mixture;
[0066] The second step is to place the mixture in a twin-screw extruder for melt extrusion, control the temperature of the twin-screw extruder to 200°C, and the speed of the screw to 300r / min. After melt extrusion, the mixture is cut, granulated, and dried to obtain a polypropylene composite material.
[0067] The preparation method of the cyclodextrin flame retardant is the same as that in Example 1.
[0068] Comparative Example 4
[0069] Preparation of polypropylene composite materials
[0070] The first step is to put 80 parts by weight of polypropylene, 1 part of zinc stearate and 2 parts of antioxidant 168 into a high-speed mixer for mixing, and stir at a speed of 1200 r / min for 1 hour. After the stirring is completed, a mixture is obtained;
[0071] The second step is to place the mixture in a twin-screw extruder for melt extrusion, control the temperature of the twin-screw extruder to 200°C, and the speed of the screw to 300r / min. After melt extrusion, the mixture is cut, granulated, and dried to obtain a polypropylene composite material.
[0072] Performance Testing
[0073] Ⅰ. With reference to the national standard GB / T2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 2: Room Temperature Test", the combustion performance of the polypropylene composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 of the present invention was tested. The test results are shown in the following table:
[0074]
[0075]
[0076] As can be seen from the above table, the limiting oxygen index of the polypropylene composite materials prepared in Examples 1 to 3 of the present invention is relatively high, indicating that the prepared composite materials have good flame retardant properties. The polypropylene composite materials prepared in Comparative Examples 2 and 3 have good flame retardancy due to the addition of cyclodextrin flame retardant, but the limiting oxygen index of the polypropylene composite material prepared in Comparative Example 2 is slightly lower than that of Comparative Example 3, because talcum powder that can play a certain flame retardant effect is not added. Comparative Examples 1 and 4 have poor flame retardant properties because cyclodextrin flame retardant is not added during the preparation of the polypropylene composite materials. However, in Comparative Example 1, a modified inorganic filler is added, so the limiting oxygen index is slightly higher than that of Comparative Example 4, and the flame retardant property of the polypropylene composite material prepared in Comparative Example 4 is the worst.
[0077] II. With reference to the national standard GB / T3960-2016 "Test Method for Sliding Friction and Wear of Plastics", the polypropylene composite materials prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 4 were tested for friction and wear performance. The wear resistance of the polypropylene composite materials was evaluated by the friction coefficient. Generally, a smaller friction coefficient indicates better wear resistance of the material. The test results are shown in the following table:
[0078]
[0079]
[0080] As can be seen from the above table, the friction coefficients of the polypropylene composite materials prepared in Examples 1 to 3 of the present invention are all small, indicating that the wear resistance of the composite materials is good. The polypropylene composite materials prepared in Comparative Examples 1 and 3 have good wear resistance because talcum powder with wear resistance is added. However, in Comparative Examples 2 and 4, no talcum powder is added during the preparation of the polypropylene composite materials, so the wear resistance of the composite materials is poor.
[0081] III. Referring to the national standard GB / T31402-2015 "Test Method for Antibacterial Performance of Plastic Surfaces", Staphylococcus aureus was selected as the test strain, and the antibacterial performance of the polypropylene composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 of the present invention was tested. The test results are shown in the following table:
[0082]
[0083] As can be seen from the above table, the antibacterial rates of the polypropylene composite materials prepared in Examples 1 to 3 are all relatively high, indicating that the prepared polypropylene composite materials have good antibacterial effects on Staphylococcus aureus. The polypropylene composite material prepared in Comparative Example 1 has good antibacterial properties due to the addition of modified inorganic fillers, while the antibacterial rates of the polypropylene composite materials prepared in Comparative Examples 2 to 4 are relatively low, because the antibacterial modified talc is not added to the preparation process of the polypropylene composite material, so the antibacterial properties are relatively poor.
[0084] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0085] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A process for preparing a polypropylene composite material, characterized in that: The following steps are involved: The first step is to put 50-80 parts by weight of polypropylene, 10-15 parts of cyclodextrin flame retardant, 0.5-1 parts of lubricant, 1-2 parts of antioxidant and 20-30 parts of modified inorganic filler into a high-speed mixer for mixing, and stir at a speed of 1000-1200 r / min for 0.5-1h. After the stirring is completed, a mixture is obtained; The preparation method of the cyclodextrin flame retardant comprises the following steps: S1: Add β-cyclodextrin and N,N-dimethylformamide to a reaction bottle equipped with a thermometer and nitrogen, mix well, then add 1,3,5-triglycidyl-S-triazinetrione and a catalyst, raise the system temperature to 70-80°C, keep the temperature for 10-14h, and after the reaction is completed, remove the solvent by vacuum distillation to obtain modified cyclodextrin; S2: Add modified cyclodextrin and tetrahydrofuran to a reaction bottle equipped with a thermometer, mix well, then add dimethyl chlorophosphate and an acid binding agent, raise the system temperature to 55-60°C, keep the temperature for 2-4 hours, and after the reaction is completed, remove the solvent by distillation under reduced pressure to obtain a cyclodextrin flame retardant; The preparation method of the modified inorganic filler comprises the following steps: A: Add talcum powder and water to a reaction bottle equipped with a thermometer, perform ultrasonic dispersion, then add 2,3-epoxypropyltrimethylammonium chloride, raise the system temperature to 60-70°C, and keep the reaction for 3-4 hours. After the reaction is completed, filter and separate the solid product, wash, and vacuum dry to obtain modified talcum powder; B: Add modified talcum powder and ethanol to a reaction bottle equipped with a thermometer, stir evenly, then add guanidine hydrochloride, raise the system temperature to 55-65°C, keep warm and react for 4-6 hours. After the reaction is completed, filter, wash, vacuum dry, grind and sieve to obtain a modified inorganic filler; The second step is to place the mixture in a twin-screw extruder for melt extrusion, control the temperature of the twin-screw extruder to be 160-200°C, and the speed of the screw to be 150-300r / min. After melt extrusion, the mixture is cut, granulated, and dried to obtain a polypropylene composite material.
2. The process for preparing a polypropylene composite material according to claim 1, characterized in that: In the first step, the lubricant is any one of magnesium stearate, zinc stearate or sodium stearate; the antioxidant is any one of antioxidant 1010 or antioxidant 168.
3. The process for preparing a polypropylene composite material according to claim 1, characterized in that: In step S1, the catalyst is any one of boron trifluoride etherate or tetrabutylammonium bromide.
4. The process for preparing a polypropylene composite material according to claim 1, characterized in that: In step S2, the acid binding agent is any one of triethylamine or pyridine.
5. The process for preparing a polypropylene composite material according to claim 1, characterized in that: In step A, the power of the ultrasound is 200-300W, and the time is 15-20min.
6. The process for preparing a polypropylene composite material according to claim 1, characterized in that: In step B, the mesh size of the sieving is 2000-3000 mesh.
Citation Information
Patent Citations
An impact-resistant and aging-resistant glass fiber reinforced polypropylene composite material and its preparation method
CN111944239B
Compound intumescent flame retardant and preparation method thereof
CN102796283A
Preparation method of cyclodextrin-based phosphated flame retardant
CN107501636A